2006
DOI: 10.1182/blood-2006-07-028282
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 2-stage platelet aggregation process mediating shear-dependent thrombus formation

Abstract: Disturbances of blood flow at sites of atherosclerotic plaque rupture are one of the key pathogenic events promoting platelet activation and arterial thrombus formation. Shear effects of platelets have been extensively investigated in vitro; however, the mechanisms by which shear promotes platelet aggregation in vivo remain incompletely understood. By employing high-resolution imaging techniques to in vitro and in vivo thrombosis models, we demonstrate a unique mechanism initiating shear-dependent platelet agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
186
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(196 citation statements)
references
References 53 publications
7
186
0
3
Order By: Relevance
“…Our previous studies indicated that megakaryocytes derived from PIP5KIg-null yolk sac progenitor cells have a defect in anchoring their integrins to the underlying cytoskeleton. 35 We also observed that this defect was dependent on the lipid kinase activity of PIP5KIg. Although our prior work suggested that PIP5KIg was important for anchoring integrins, this study did not analyze membrane dynamics in a cell that required integrins for their principal function.…”
Section: Results P90 But Not the P87 Splice Variant Of Pip5kig Colocamentioning
confidence: 55%
See 1 more Smart Citation
“…Our previous studies indicated that megakaryocytes derived from PIP5KIg-null yolk sac progenitor cells have a defect in anchoring their integrins to the underlying cytoskeleton. 35 We also observed that this defect was dependent on the lipid kinase activity of PIP5KIg. Although our prior work suggested that PIP5KIg was important for anchoring integrins, this study did not analyze membrane dynamics in a cell that required integrins for their principal function.…”
Section: Results P90 But Not the P87 Splice Variant Of Pip5kig Colocamentioning
confidence: 55%
“…In addition, it has been postulated that platelets regulate the elasticity of their cell membranes during the initial phases of platelet adhesion. 35 Therefore, we reasoned that PIP5KIg might contribute to the regulation of integrins and cell elasticity in platelets. We observed by using an optical trap that PIP5KIg E17 2/2 PF4 Cre 1 platelets had a defect in anchoring their integrins to the underlying actin cytoskeleton ( Figure 3B).…”
Section: Results P90 But Not the P87 Splice Variant Of Pip5kig Colocamentioning
confidence: 99%
“…59 ADP released from dense granules regulates a-granule secretion, [60][61][62] forming dense regions that stabilize the platelet aggregate. 63 Concomitant release of polyP with ADP from dense granules suggests that it may be retained in these low-solute transport areas. a-Granule release occurs at lower agonist concentrations than dense granule release, 64,65 suggesting that platelets at the edge of the core and within the shell may release fibrinogen and bind fibrin before polyP secretion, thereby providing an anchor to retain polyP in the locale of the activated platelet aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the chronological implication of these platelet activators and their intracellular signaling may be contributing factors, because platelet aggregation is a sequential process, with reversible and irreversible steps. [42][43][44] Therefore, inhibition of thrombin by apelin may affect all potential thrombin downstream effectors involved in platelet activation. Furthermore, the inability of apelin to inhibit platelet activation in the presence of TXA 2 or ADP may be related to ADP/TXA 2 intracellular signaling pathways that are not regulated by apelin or to those that may interfere with the apelin signaling.…”
Section: Discussionmentioning
confidence: 99%